Impacts of Environmental Change and Microplastic Pollution on Zooplankton - Dong, Xiangyi (Transactions on Environment, Energy and Earth Sciences, 2024)
Zooplankton are an important part of the ecosystem, carrying out the function of energy transfer in the food web, linking the lower to the higher trophic levels of species. They are often under the combined influence of the surrounding environment and other aquatic life. This research aims to study the effects of environmental changes, such as changes in the several properties of seawater, microplastic pollution on zooplankton populations and the interactions between other aquatic organisms and zooplankton. The results show that with environmental changes, the increase in sea temperature, pH value, eutrophication of seawater and the increase of microplastic pollution will harm the zooplankton population. At the same time, the size of zooplankton populations can affect the number of fish that feed on them, and the predation of fish can also affect their biomass and population structure. These studies can help humans better understand the mechanisms of ecosystem interactions in nature, assess and predict broader environmental change, maintain healthy ecosystems, and ensure future resource sustainability.